THE IMPACT OF TEACHER TRAINING ON STUDENTS’ LEARNING - Shermamatova , Zaynab Azimjonovna; Akhadova, Ugiloy Kilich kizi; Ummatova , Marjona Gafur kizi (Educational Research in Universal Sciences, 2023)
In the contemporary era, the impact of teachers on shaping the personality of students, referred to as specialists hereafter, is highly relevant. Education today is a creative endeavor that unlocks new horizons for cultural development. The intricate interplay between culture and education is indispensable for the advancement of secondary and higher education, as well as for the personal and creative accomplishments of both teachers and students.